PENINGKATAN PEMAHAMAN MATERI BANGUN DATAR MELALUI BAHAN AJAR AUDIO VISUAL BERBASIS MACROMEDIA FLASH PADA SISWA KELAS IV MI AMANATUL IZZAH CANGKRING KREMBUNG SIDOARJO - Makrifah, Nurul; Latifah, Nur (At-Turost : Journal of Islamic Studies, 2022)
The understanding of grade IV students of MI Amanatul Izzah on the material of flat shapes is included in the low category with pre-cycle scores of 10 grade IV students only 30% who complete the student understanding test. The solution to overcome these problems is through macromedia flash-based audio-visual teaching materials. The research objectives: 1) To find out the application of macromedia flash-based audio-visual teaching materials in improving the understanding of flat shape material for fourth grade students of MI Amanatul Izzah, 2) To determine the improvement of understanding of flat-shaped materials through macromedia flash-based audio-visual teaching materials for fourth grade students. MI Amantul Izzah. The research method used is CAR using Kurt Lewin's model in which each cycle consists of four main components, namely: 1) Planning, 2) Action, 3) Observation, and 4) Reflection. The results of the study on the application of macromedia flash-based audio-visual teaching materials to the fourth grade students of MI Amanatul Izzah were very good. This can be seen from the results of the final value of the teacher's activity in the first cycle of 61.71 and the second cycle of 79.68. The final score of student activity in the first cycle is 62 and the second cycle. The average value of the pre-cycle class was 65.64, the first cycle was 70.42 and the second cycle was 90.78. The percentage of pre-cycle learning completeness is 30%, the first cycle is 70%, the second cycle is 90% with a very good category and has met the specified performance indicators.